Zytux in Refractory Myasthenia Gravis: A Multicenter, Open-Labeled, Clinical Trial Study of Effectiveness and Safety of a Rituximab Biosimilar - Fatehi, Farzad; Moradi, Kamyar; Okhovat, Ali Asghar; Shojatalab, Ghazaleh; Sedighi, Behnaz; Boostani, Reza; Sarraf, Payam; Haghi Ashtiani, Bahram; Ghasemi, Majid; Moussavi, Soussan; Anjidani, Nassim; Nafissi, Shahriar (Frontiers in Neurology, 2021)
Objectives: Myasthenia gravis (MG) is an immune-mediated neuromuscular disorder responsive to immunomodulatory treatments. 10-20% of MGs are not responsive to conventional first-line therapies. Here, we sought to investigate the efficacy and safety of Rituximab therapy in the treatment of patients with refractory MG. Methods: In a 48-week, multicenter, open-labeled, prospective cohort setting, 34 participants with refractory MG were assigned to receive infusions of Zytux, which is a rituximab biosimilar, according to a validated protocol. Clinical, functional, and Quality of life (QoL) measurements were recorded at baseline, and seven further visits using the Myasthenia Gravis Foundation of America (MGFA), Myasthenia Gravis Composite (MGC), Myasthenia Gravis Activities of Daily Living profile (MG-ADL), and Myasthenia Gravis Quality of Life (MGQoL-15) scales. Besides, the post-infusion side effects were systematically assessed throughout the study. Results: The correlation analysis performed by Generalized Estimating Equations (GEE) analysis represented a significant reduction of MGC, MG-ADL, and MGQoL-15 scores across the trial period. The subgroup analysis based on the patients' clinical status indicated a significant effect for the interaction between time and MGFA subtypes on MG-ADL score, MGC score, and pyridostigmine prednisolone dose, reflecting that the worse clinical condition was associated with a better response to rituximab. Finally, no serious adverse event was documented. Conclusions: Rituximab therapy could improve clinical, functional, and QoL in patients with refractory MG in a safe setting. Further investigations with larger sample size and a more extended follow-up period are warranted to confirm this finding.